EDUKASI GIZI PADA IBU HAMIL DI KELURAHAN PISANG KECAMATAN PAUH KOTA PADANG - Desmawati Desmawati; Abdiana Abdiana; Edison Edison; Wahyu Kodri A; Rian Rizki Ananda; Pandu Prakoso Moendanoe; Zikra Fadhilah; Karolina Karolina; Doa Vami; Rahmeidia Audya Yusmi; Qorirah Summayah Indrapati; Nurul Fadhilah; Mona Indah Putriani (BULETIN ILMIAH NAGARI MEMBANGUN, 2021)
Chronic Energy Deficiency is a problem in pregnant women whose prevalence fluctuates and can hurt the baby to be born. This activity aims to provide counseling and education to pregnant women with Chronic Energy Deficiency who are in the working area of the Pauh Health Center, precisely in Pisang Village, to find out, understand and apply knowledge about good nutritional intake for pregnant women to reduce the incidence of intrauterine growth retardation caused by can lead to the poor nutritional status of children. This activity was carried out in the Pisang Village, Pauh District, Padang City, involving all related sectors. This activity is in the form of a series of events in cadre training and counseling for pregnant women with chronic energy deficiency, preceded by a pretest, launching a class for pregnant women, cooking demonstrations, and pregnancy consultations. The activities after the event were post-tested to assess the increase in knowledge of pregnant women and cadres. The increase in the level of knowledge of pregnant women after good nutrition counseling in pregnancy from 54.5% to 63.6% was classified as good, 36.3% to 27.2% was classified as sufficient, and 9% had less knowledge. The program to help standby nutrition intake for mothers with chronic energy deficiency has been proven to increase knowledge of pregnant women and cadres about the importance of nutrient intake in preventing chronic energy deficiency in pregnant women, as well as the importance of nutrition for pregnant women with chronic energy deficiencies so that it does not affect the babies they contain